Paradigm Revolution and Ideological Confrontation: A Review of Hu Shi’s Zhuangzi Studies - Li, Jiawu (International Journal of Social Sciences and Public Administration, 2026)
Hu Shi’s research on Zhuangzi holds a paradigm-shifting significance in the 20th-century history of Zhuangzi studies in China. His research unfolds across four core dimensions: first, excavating and critiquing Zhuangzi’s "theory of biological evolution" through the lens of evolutionism; second, assailing Zhuangzi’s "broad-minded" (daguanzhuyi)philosophy of life from the standpoint of experimentalism; third, conducting a comparative analysis between Zhuangzi and Spinoza to explore Sino-Western parallels; and fourth, creatively transforming the Lao-Zhuang concept of "non-action" (wuwei) into a modern liberal idea for limiting government power and safeguarding freedom, advocating a practical model of "expert planning, government non-action." This body of research profoundly reflects Hu Shi’s "interpreting China through the West" methodology and the intertwining of Enlightenment concerns and pragmatic orientations in his thought. While his work paved the way for the modern transformation of traditional scholarship, its limitations, such as the tendency to analogize with Western learning and serve immediate practical concerns, also provide an important cautionary lesson for later generations.